Review of high-intensity interval training for cognitive and mental health in youth - Leahy, A. A.; Mavilidi, M. F.; Smith, J. J.; Hillman, C. H.; Eather, N.; Barker, D.; Lubans, D. R. (Medicine & Science in Sports & Exercise, 2020)
Purpose: High-intensity interval training (HIIT) has emerged as a time-efficient strategy to improve children`s and adolescents` health-related fitness in comparison to traditional training methods. However, little is known regarding the effects on cognitive function and mental health. Therefore, the aim of this systematic review was to evaluate the effect of HIIT on cognitive function (basic information processing, executive function) and mental health (well-being, ill-being) outcomes for children and adolescents. Methods: A systematic search was conducted, and studies were eligible if they 1) included a HIIT protocol, 2) examined cognitive function or mental health outcomes, and 3) examined children or adolescents (5-18 yr). Separate meta-analyses were conducted for acute and chronic studies, with potential moderators (i.e., study duration, risk of bias, participant age, cognitive demand, and study population) also explored. Results: A total of 22 studies were included in the review. In acute studies, small to moderate effects were found for executive function (standardized mean difference [SMD], 0.50, 95% confidence interval [CI], 0.03-0.98; P = 0.038) and affect (SMD, 0.33; 95% CI, 0.05-0.62; P = 0.020), respectively. For chronic studies, small significant effects were found for executive function (SMD, 0.31; 95% CI, 0.15-0.76, P < 0.001), well-being (SMD, 0.22; 95% CI, 0.02-0.41; P = 0.029), and ill-being (SMD, -0.35; 95% CI, -0.68 to -0.03; P = 0.035). Conclusions: Our review provides preliminary review evidence suggesting that participation in HIIT can improve cognitive function and mental health in children and adolescents. Because of the small number of studies and large heterogeneity, more high-quality research is needed to confirm these findings. Übersicht über hochintensiven Intervalltrainings für die kognitive und psychische Gesundheit bei Jugendlichen